2014
DOI: 10.4236/fns.2014.510096
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Components of Tomato Accelerate Alcohol Metabolism by Increasing Pyruvate Level

Abstract: Consumption of food while drinking alcohol has been suggested to play important roles in alleviating the physiological and pharmacological influences of alcohol. Vegetables are believed to provide health benefits, but there is little evidence for their influence on the effects of alcohol consumption. The present study aimed to investigate the effect of a common vegetable, tomato, on alcohol metabolism. In a randomized, controlled, crossover study with12 Japanese healthy men aged between 24 and 56 years, drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…First, the ethanol molecule is converted into acetaldehyde (AA), a highly toxic metabolite mediating alcohol “hangover” symptoms (headache, nausea, and tachycardia), by hepatic cytosolic alcohol dehydrogenase, ADH. Further, AA is transformed into acetic acid, a nontoxic metabolite [ 35 , 36 ], by mitochondrial aldehyde dehydrogenase type 2 (ALDH-2) highly expressed in liver and to a lesser extent in other tissues (muscles, brain). Although we did not measure activity of ADH and ALDH-2 in the subjects enrolled, the pattern of changes in serum EtOH and AA concentrations seen in the volunteers allows us to make some projections.…”
Section: Discussionmentioning
confidence: 99%
“…First, the ethanol molecule is converted into acetaldehyde (AA), a highly toxic metabolite mediating alcohol “hangover” symptoms (headache, nausea, and tachycardia), by hepatic cytosolic alcohol dehydrogenase, ADH. Further, AA is transformed into acetic acid, a nontoxic metabolite [ 35 , 36 ], by mitochondrial aldehyde dehydrogenase type 2 (ALDH-2) highly expressed in liver and to a lesser extent in other tissues (muscles, brain). Although we did not measure activity of ADH and ALDH-2 in the subjects enrolled, the pattern of changes in serum EtOH and AA concentrations seen in the volunteers allows us to make some projections.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ushida et al reported that the concentrated aqueous fraction of tomato decreased BEC in rats [24]. The difference between these results may be caused by the degree of the condensation (Brix) of aqueous components in each tomato sample.…”
Section: Discussionmentioning
confidence: 96%
“…It seems unlikely that WIF accelerated alcohol metabolism; thus, we suspect that WIF inhibited alcohol absorption in the gastrointestinal tract. Ushida et al previously reported that the administration of a concentrated tomato supernatant attenuates elevated BEC [ 22 ]. However, the enriched water-soluble components were present in a concentrated tomato supernatant solution containing 11.3% glucose and 10.7% fructose.…”
Section: Discussionmentioning
confidence: 99%